Kritik ekologis dalam Novel Memburu Kasih Perempuan Sampan Karya Abdul Kadir Ibrahim - Leoni, Tessa Dwi (Kajian Linguistik dan Sastra, 2024)
This research aims to uncover ecological criticism in the novel "Memburu Kasih Perempuan Sampan" by Abdul Kadir Ibrahim. This research is a descriptive qualitative study using an ecocritical perspective to describe the data in depth. The data in this study consists of sentences that contain issues related to environmental damage found in the novel. Data were collected through repeated reading stages, then classified, analyzed, and concluded. The results of this research show that there are three forms of ecological criticism in the novel "Memburu Kasih Perempuan Sampan," including: criticism of the issue of sand resource exploitation, criticism of illegal logging, and the issue of the impact of exploitation on nature and the lives of local communities.